2013
DOI: 10.1177/1941738113491701
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Migraine Versus Concussion

Abstract: Context:An era of increased awareness of sports concussions may decrease a provider’s ability to diagnose the athlete’s actual condition and may ultimately prolong the restriction of the injured athlete from sports. Trauma-triggered migraine is a source of headaches, especially in athletes with a family history of migraines.Evidence Acquisition:Research articles were primarily obtained through the electronic database PubMed from 1993 to August 2012. Primary research parameters included trauma-induced headaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The use of TCAs is recommended in patients presenting insomnia and PTH. Among the TCA drugs, amitriptyline is an effective antimigraine therapy, which induces sedation but presents adverse events such as dizziness, dry eyes and mouth, constipation and increased appetite and cardiac adverse events with onset arrhythmia and an extension of the QT interval [57]. The properties of amitriptyline include anti-anxiety and anti-depressant effects and sleep promoting which are characteristics of PTH [56].…”
Section: Tricyclic Antidepressants Drugsmentioning
confidence: 99%
“…The use of TCAs is recommended in patients presenting insomnia and PTH. Among the TCA drugs, amitriptyline is an effective antimigraine therapy, which induces sedation but presents adverse events such as dizziness, dry eyes and mouth, constipation and increased appetite and cardiac adverse events with onset arrhythmia and an extension of the QT interval [57]. The properties of amitriptyline include anti-anxiety and anti-depressant effects and sleep promoting which are characteristics of PTH [56].…”
Section: Tricyclic Antidepressants Drugsmentioning
confidence: 99%
“…In the majority of cases, the visual aura precedes the onset of headache but in selected cases can accompany the headache and be prolonged or can occur without headache. Studies have demonstrated considerable overlap between the symptoms of migraine headaches and SRC (30,43). Although acute SRC patients rarely meet the International Classification of Headache Disorders (ICHD)-3-beta criteria for migraine headaches, symptoms, such as headache, nausea, photophobia, phonophobia, and blurred vision, are commonly endorsed by these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, trauma-triggered migraine [5] and status migrainosus are complication of migraine without aura. They have their own distinct clinical profiles.…”
Section: Classificationmentioning
confidence: 99%